Apoptosis - Reed, John C. (Methods in enzymology, 2000)
Volume 322 of Methods in Enzymology is dedicated to apoptosis. Major topics covered include measuring apoptosis and apoptosis-induced endonucleases, measuring apoptosis in lower organisms, proteases involved in apoptosis and their inhibitors, cell free systems for monitoring steps in apoptosis pathways, mitochondria and apoptosis, bCl-2 family proteins, and studying receptors and signal transduction events implicated in cell survival and cell death. The critically acclaimed laboratory standard for more than forty years, Methods in Enzymology is one of the most highly respected publications in t